Faith in the Digital Age: Factors Influencing Social Media Use among Indonesian Churches - Katili, Funixman (Jurnal Teologi Cultivation, 2024)
As digital connectivity increases in Indonesia, Protestant churches face growing pressure to integrate social media into their ministry, especially within the context of Christian Religious Education (CRE). While digital tools offer expanded avenues for communication and faith formation, a notable digital divide persists among Indonesian Protestant churches, hindering consistent engagement with digital platforms such as Facebook, Instagram, YouTube, and WhatsApp. This divide raises critical questions about what internal factors influence a church’s digital adoption. This study employed a quantitative descriptive survey method to analyze key predictors of social media adoption across 150 Protestant churches in five major Indonesian provinces. Data were collected through structured questionnaires, measuring variables such as church size, youth demographic proportions, clergy digital literacy, and synodical support. Binary logistic regression analysis was used to assess the influence of each variable on a church's likelihood to regularly adopt social media for ministry purposes. Findings indicate that three primary factors significantly influence social media adoption: (1) the digital literacy of church leaders, (2) the size of the church organization, and (3) the percentage of young congregants. Churches with digitally literate clergy, larger congregational size, and a higher proportion of youth were substantially more likely to maintain an active social media presence. While denominational support did not show direct statistical significance, it contributed indirectly by fostering digital awareness and providing training infrastructure. The digital divide among Indonesian Protestant churches is largely driven by disparities in human capacity and organizational readiness, rather than technological access. Enhancing digital literacy among clergy and leveraging youth engagement are essential strategies for bridging this gap. Furthermore, synods and theological institutions play a vital enabling role in sustaining digital transformation within faith communities, positioning social media not as a threat but as a strategic extension of the church’s educational and spiritual mission.